Community Knowledge and Stigma Against COVID-19 Phase III Vaccine (Booster) and Health Workers in Handling COVID-19 in Parepare City - Ainun Tatang, Nuraini; Yusuf, Syarifuddin; Anggraeny, Rini (Indonesian Health Journal (IHJ), 2023)
The COVID-19 pandemic has caused fear among some people. Feelings of fear can make a person alert. However, when the feeling of fear becomes excessive, it can create a negative impression. This study aimed to determine the level of knowledge and stigma of the people of Parepare City towards the Phase III COVID-19 vaccine (Booster). This research is a descriptive study using a quantitative approach. The tool used in data collection is a questionnaire. This research was conducted in Parepare City from 11 to July 18, 2022. The population in this study were all people living in Parepare City, totaling + 154,524 people. The sample or sampling technique uses accidental sampling and 100 samples. Data were analyzed univariately and presented in the form of a frequency distribution. Research shows that the level of public knowledge of the Phase III vaccine (Booster) is 63%. The level of public knowledge of health workers in handling COVID-19 is in the high category of 73%. The stigma level of the people of Parepare City towards the Phase III vaccine (Booster) is in the high category of 69%. The level of community stigma towards health workers in handling COVID-19 is in the high category of 78%. In general, the people of Pare-pare City have high knowledge of the stage III vaccine (Booster) and health workers. However, implementing the Phase III vaccine (Booster) is still low due to the high stigma of the people of Parepare City towards health workers and Phase III vaccines (Boosters).